Managing the principles of good governance: evidence of members recruitment in the Indonesian police on 2015-2019 - Setyadi, Rakhmad; Yuwono, Teguh; Rahayu, Rahayu; Dwimawanti, Ida Hayu (Management and Entrepreneurship: Trends of Development, 2022)
The purpose of this research is to analyze the problems of the National Police in managing the principles of good governance through the principles of Clean, Transparent, Accountable, and Humanist in the recruitment of Polri members in 2015-2019. As well as to analyze aspects of the obstacles and challenges of the National Police in the application of the principles of Clean, Transparent, Accountable, and Humanist (CTAH) in the recruitment of members of the Police. And formulate or produce an ideal Polri member recruitment model in accordance with the principles of good governance. This study uses a qualitative method. Data was collected by means of a literature study, a document study, and in-depth interviews before data analysis was carried out. The results showed that the recruitment system used was a decentralized system with an indication of the powers granted to the regions. In its implementation it is transparent and objective so that healthy competence is achieved in order to prevent deviations or abuse of authority by paying attention to the principles of Clean, Transparent, Accountable and Humanist First there must be fixed the culture of the bearer of the function of human resource development itself and improve the quality of Polri personnel. It also requires a moral commitment between each party related to the development of Polri's human resources to be able and willing to carry out the process of developing human resources in a transparent, integrity, accountable, and professional manner.JEL Classification: I380, L310, L440